Antifungal stewardship in a tertiary-care institution: a bedside intervention. (May 2015) - Valerio, M.; Muñoz, P.; Rodríguez, C.G.; Caliz, B.; Padilla, B.; Fernández-Cruz, A.; Sánchez-Somolinos, M.; Gijón, P.; Peral, J.; Gayoso, J.; Frias, I.; Salcedo, M.; et al.
Abstract: Antifungal stewardship (AFS) programmes are needed in tertiary-care hospitals. Our aim is to describe a bedside non-restrictive AFS programme, and to evaluate its economic impact. During the first year of the AFS a bundle of non-interventional measures were implemented. During the second year an infectious diseases specialist visited 453 patients receiving candins, liposomal amphotericin B, voriconazole or posaconazole. Monthly costs were studied with an interrupted time series (ITS) analysis. The main prescribing departments were haematology (35%), medical departments (23%), and intensive care units (20%). Reasons to start antifungal therapy were: targeted therapy (36%), prophylaxis (32%), empirical therapy (20%) and pre-emptive therapy (12%). At the initial visit, diagnostic advice was provided in 40% of cases. The most common therapeutic recommendations were to de-escalate the antifungal drug (17%) or to suspend it (7%). Annual total antifungal expenditure was reduced from US$3.8 million to US$2.9 million over the first 2 years, generating net savings of US$407, 663 and US$824, 458 per year after considering the cost of additional staff required. The ITS analyses showed a significant economic impact after the first 12 months of the intervention (p 0.042 at month 13), which was enhanced in the following 24 months (p 0.006 at month 35). The number of defined daily doses decreased from 66.4 to 54.8 per 1000 patient-days. Incidence of candidaemia was reduced from 1.49 to 1.14 (p 0.08) and related mortality was reduced from 28% to 16% (p 0.1). A collaborative and non-compulsory AFS program based on bedside intervention is an efficacious and cost-effective approach that optimizes the use of AF drugs.